2(x+7)+23=9-3(x-1)

Simple and best practice solution for 2(x+7)+23=9-3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+7)+23=9-3(x-1) equation:


Simplifying
2(x + 7) + 23 = 9 + -3(x + -1)

Reorder the terms:
2(7 + x) + 23 = 9 + -3(x + -1)
(7 * 2 + x * 2) + 23 = 9 + -3(x + -1)
(14 + 2x) + 23 = 9 + -3(x + -1)

Reorder the terms:
14 + 23 + 2x = 9 + -3(x + -1)

Combine like terms: 14 + 23 = 37
37 + 2x = 9 + -3(x + -1)

Reorder the terms:
37 + 2x = 9 + -3(-1 + x)
37 + 2x = 9 + (-1 * -3 + x * -3)
37 + 2x = 9 + (3 + -3x)

Combine like terms: 9 + 3 = 12
37 + 2x = 12 + -3x

Solving
37 + 2x = 12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
37 + 2x + 3x = 12 + -3x + 3x

Combine like terms: 2x + 3x = 5x
37 + 5x = 12 + -3x + 3x

Combine like terms: -3x + 3x = 0
37 + 5x = 12 + 0
37 + 5x = 12

Add '-37' to each side of the equation.
37 + -37 + 5x = 12 + -37

Combine like terms: 37 + -37 = 0
0 + 5x = 12 + -37
5x = 12 + -37

Combine like terms: 12 + -37 = -25
5x = -25

Divide each side by '5'.
x = -5

Simplifying
x = -5

See similar equations:

| -10+9d=8 | | 7x-13=10x+8 | | x^2*36=y^2 | | 0.5*x^3-0.5*x-3=0 | | sin(2t)=-0.56 | | 4x+y=-27 | | 4sen^2(x)-8sen(x)-5=0 | | y+8=0.1(x-3) | | 172n=184 | | y-1=0.2(x+3) | | y+4=10(x-3) | | 361n=130 | | 4-(2x-11)= | | 130n=361 | | 575n=980 | | 361n=172 | | 2(v-3)=9v+36 | | 8u+32+3u=-23 | | 2x=5(2-4x) | | 1/sinh(x) | | ln(x^2-25)=10+ln(75) | | X^5/15×X^7/15 | | 3(a+2)+2(4+b)= | | (k-1)x^2-2kx+k^2=0 | | -2v+8(v-3)=-6 | | (k+1)x^2-2kx+k^2=0 | | 7+2x=8-5(3+x) | | 7x+7x+6b= | | 6+w=-12+2w | | -3(y+6)=-45 | | 8a-2b+4-3b+a-3= | | y-9=0.3(x+2) |

Equations solver categories